Dissociative Amnesia or Malingered Amnesia? A Case Report. Issue 2 (14th March 2016) - Marcopulos, Bernice A.; Hedjar, Laysa; Arredondo, Beth C.
ABSTRACT: Dissociative amnesia is a rare and perplexing psychiatric disorder with purported "functional" or neurological origins—or is it simply malingering? We report a Jane Doe who was admitted to a psychiatric hospital and treated for dissociative amnesia or fugue with group therapies and psychotropic medication for six months. She was referred for neuropsychological assessment to evaluate memory loss for her past and her identity. The Test of Memory Malingering and the Structured Inventory of Malingered Symptomatology suggested feigned memory deficits. The hospital eventually learned Jane Doe's identity. She was wanted for a crime in another state, but also had a psychiatric history with several hospitalizations. When confronted, she admitted her deception. This case illustrates the importance of using formal testing and consulting the scientific literature on memory for discerning true versus feigned memory deficits. This case also points out that mentally ill defendants can malinger other disorders. We review the pertinent literature on the cognitive neuroscience of autobiographical memory, and its ability to inform forensic mental health evaluations.